Analisis Penggunaan Solar Tracking dan Watercooling pada Daya Output Panel Surya - sri, ida ayu; Supriono; Aji Mubarak, Muhammad (DIELEKTRIKA, 2025)
This study aims to analyze the performance of a 5 Wp polycrystalline solar panel 280×185×17 mm equipped with a solar tracking system and water cooling. The solar tracker optimizes sunlight capture using a Light Dependent Resistor (LDR) sensor and a servo motor as the actuator, while the water cooling system stabilizes the module temperature through water circulation with a pump and relay. Solar irradiance was measured using a pyranometer, while voltage and current were recorded every 15 minutes. The results show that the maximum power output was achieved at 09:45, reaching 5.44 W at an irradiance of 679.256 W/m² and a temperature of 36 °C. The average power output was 3.87 W under an average irradiance of 416.96 W/m², with a voltage of 5.18 V and current of 0.74 A. The implementation of solar tracking and water cooling effectively increased light absorption, maintained temperature stability.